2019
DOI: 10.2147/cmar.s226459
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of Double Sleeve Lobectomy by Uniportal Video-Assisted Thoracic Surgery (VATS) and Thoracotomy for NSCLC Treatment</p>

Abstract: BackgroundWith the development of the surgical technique and experience of surgeons, uniportal VATS has been used in double sleeve lobectomy to treat non-small cell lung cancer (NSCLC). This retrospective study aims to evaluate the efficacy and safety of uniportal VATS in NSCLC treatment.MethodsWe reviewed 42 NSCLC patients who underwent double sleeve lobectomy in Shanghai Pulmonary Hospital from June 2015 to November 2017. 21 patients received double sleeve lobectomy through uniportal VATS and 21 through conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 36 publications
0
35
0
1
Order By: Relevance
“…As such, the experience required to undertake complex uniportal VATS sleeve lobectomies is even greater (6). Uniportal VATS complex sleeve lung resections need to follow the conventional surgical techniques for uniportal VATS sleeve lung resection, which have been summarized in previous articles (7)(8)(9)(10)(11)(12). However, special techniques should be applied according to the characteristics of the complex sleeve surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the experience required to undertake complex uniportal VATS sleeve lobectomies is even greater (6). Uniportal VATS complex sleeve lung resections need to follow the conventional surgical techniques for uniportal VATS sleeve lung resection, which have been summarized in previous articles (7)(8)(9)(10)(11)(12). However, special techniques should be applied according to the characteristics of the complex sleeve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment methods for blood vessels, pulmonary fissures, and lymph nodes were the same as for complete thoracoscopic lobectomy. The specific steps were as follows: sleeve bronchial resection, anastomosis trimming, and frozen pathological examination to ensure that there was no tumor infiltration at the incision margin; then 3-0 (tracheal and leaf bronchial anastomosis) or 4-0 (segmental bronchial anastomosis) non-absorbable sutures (prolene, Covidien Inc., USA) were sutured continuously in clockwise and counterclockwise directions from the medial wall, respectively, sutured from the back of the anastomotic site to the front, knotted after suturing, and tested through flushing for no leakage even when the airway pressure was maintained at 30 cmH 2 O. Uniportal VATS special sleeve lung resection needs to follow the conventional surgical technique of uniportal VATS sleeve lung resection, which has been summarized in previous articles (7)(8)(9)(10)(11)(12).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Since sleeve lobectomy via thoracoscopy was firstly attempted in 2002 (12), several researches reported the successful implementation of this procedure in hand of experienced surgeons (13)(14)(15)(16). Recently, a series of comparative studies further identified the feasibility of thoracoscopic sleeve lobectomy for centrally located NSCLC (17)(18)(19)(20)(21)(22). However, its operative safety and oncologic efficacy compared to thoracotomy sleeve lobectomy remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Video-assisted thoracic surgery (VATS) has been widely applied to treat lung cancer (50,51). A large number of previous studies have demonstrated that compared with thoracotomy, thoracoscopic lobectomy is characterized by less trauma, faster postoperative recovery and fewer complications (52).…”
Section: Surgerymentioning
confidence: 99%